(3QSGdI GdTeYIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3heKdgG ai GdJhMjO heKd MOhOgG Ydi GdeSdc GdKGdK hQaYJ Edi GdMVQI GddGghJjI hCWdbJ HCeQ ehdGfG GdMGce GdMcje s
(3BNQgG (B:s
(3aEdi YHOg GdHGFS GdabjQ aeG cGf ajg ef UhGH aef Jhajb Gdehdi haGFO bGFe GdReGf heG cGf ajg ef Rdd hNWC aef GdYHO GdNWC hGdMeO dehdGfG hMOg hGdTcQ ddEeGe GdgGOi YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B39s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds